Nonlinear relaxation in redox processes in ionic and polar liquids - Streeter, I; Lynden-Bell, R; Compton, R (2008)
Simulations have been performed to investigate the relaxation dynamics of the solvent around probe ions in the ionic liquid dimethylimidazolium hexafluorophosphate and in the polar liquid acetonitrile. The time scale of the relaxation dynamics is found to be different in the two cases, although our earlier work showed that the Marcus free energy curves, solvent rearrangement energies, and redox activation free energies were very similar. We also observe differences between the nonequilibrium decay curves S(t) and the time correlation functions C(t) for fluctuations at equilibrium showing that the response is strongly nonlinear. Relaxation toward equilibrium is slower for processes in which the magnitude of the electrostatic interaction increases than when it decreases. We discuss whether this may affect the rate constants for electrochemical processes and how this could be observed. © 2008 American Chemical Society.